Effect of breed, storage temperature and storage duration on chicken egg quality - Mohd Aris, Siti Nurizzah (2017)
This study was conducted to determine the effects of storage at 7 durations (0 or controls ,7,14,21,28,35 and 42 days ) and 3 temperature levels (Chiller storage 8◦c-9◦c, cool room temperature 16◦C and room temperature 28◦C- 31◦C ) on quality of village chicken and commercial layer breed eggs. 63 eggs from both of the breed were utilize. All hens were managed under battery cage system and fed with poultry layer mash. The eggs quality determinations were based on generally are external and internal egg quality. The external parameter is weight loss meanwhile the internal egg quality factor determined were haugh unit and yolk color. There were significantly difference (P<0.05) for all the parameters in comparison with the control .